Performance analysis of topic detection algorithms in distributed environment - Lu DENG; Yan JIA; Binxing FANG; Bin ZHOU; Tao ZHANG; Xin LIU (Tongxin xuebao)
Social network has become a way of life,therefore more and more people choose social network to express their views and feelings.Quickly find what people are talking about in big data gets more and more attention.And a lot of related methods of topic detection spring up in this situation.The performance analysis project was proposed based on the characteristics of social network.According to the project,the performances of some typical topic detection algorithms were tested and compared in large-scale data of Sina Weibo.What’s more,the advantages and disadvantages of these algorithms were pointed out so as to provide references for later applications.